Alterations of blood-brain barrier functions and gene expression during Toxoplasma gondii infection - Harun, Mohammad Syamsul Reza (2019)
The apicomplexan protozoan parasite Toxoplasma gondii is the causative agent of toxoplasmosis, a major zoonotic infection that can infect roughly one-third of the world’s human population. T. gondii is remarkable in its ability to rapidly disseminate via the bloodstream or within immune cells to immune-privileged sites distant from the site of initial infection. It can cross the blood-brain, blood-retinal and blood-placental barriers. A better understanding of the mechanisms underpinning the parasite’s interaction with these barriers is crucial for the development of therapeutic interventions. Initial work in this thesis characterises the interaction of T. gondii with human brain microvascular endothelial cells (hBMECs) evaluated using Alamar blue viability assay, FITC-dextran flux-based permeability assay, transendothelial electrical resistance (TEER) measurements for tight junction integrity evaluation, viability, early/late apoptosis and cell cycle analyses using NC-3000™ image-based flow cytometry and tight junction genes (Occludin, PRKCA and ZO-1) and inflammatory genes (IL-6, P-GP and TNF-alpha) genes expression using RT-PCR. These experiments were performed at 3, 6, 24, 48 and 72 hours post infection (h.p.i) to represent early (3 and 6 h.p.i), middle (24 h.p.i) and late (48 and 72 h.p.i) stages of infection at blood brain barrier (BBB). During the early and middle stages of infection, T. gondii maintained host cells’ viability, suppressed cell apoptosis by halting cells at the G0/G1 stage, induced up-regulation of IL-6 gene, reduced the permeability of infected cells compared to non-infected cells. Late stage of infection was marked by significant reduction of the cell integrity and vitality, and by significant increase of fragmented DNA. Initial data lead to the hypothesis that analysis of the transcriptomic changes in hBMECs in response to T. gondii infection would reveal some facets of the molecular mechanisms underlying signalling mechanisms that mediate the parasite-hBMECs interaction. To test this hypothesis, global transcriptome (i.e. gene expression) of both host hBMECs and the parasite during infection were examined in a time course study. Total RNA samples from T. gondii RH-infected hBMECs were obtained at 6, 24 and 48 h.p.i where messenger RNA (mRNA) and small RNA were sequenced using Illumina™ next-generation sequencing. MRNA and small RNA sequencing reads were mapped to the annotated human and T. gondii reference genomes before conducting differential expression analysis on control (uninfected) versus infected cell reads. Genes expressed with false discovery rate (FDR) < 0.01 and > 1 log2 fold change were identified. Differently expressed genes were then validated with microarray and quantitative real-time PCR (RT-PCR). This study confirmed previous findings that T. gondii infection halts cell cycle progression and modulates the expression of cancer-like genes in infected cells. Integrated mRNA/miRNA expression profiling and pathway analysis showed multiple signalling pathways including, ATF4 activation, TP53 regulation, selenoamino acid metabolism and selenocysteine synthesis as key pathways regulated during T. gondii infection. Small RNA study identified increased expression of miR-7, miR-19, miR-20 families and expression of the miR-17-92 family that possibly determine the fate of host cells in T. gondii infection. Also, T. gondii’s ribosomal proteins L36 and S12 were identified as key players in its pathogenesis and have good potential as vaccine candidates. Because Wnt signalling pathway was one of the most affected pathways, its role of Wnt pathway in T. gondii infection was further investigated by examining the anti-parasitic effects of Monensin, an inhibitor of the host cell WNT signalling pathway, on T. gondii tachyzoites and the proliferation of hBMECs and microglial cells. Monensin showed significant anti-T. gondii activity against the tachyzoite grown in cerebral endothelial cell and microglial cell cultures. However, inhibition of T. gondii infection in hBMECs was not directly achieved through blocking WNT signalling. Interestingly, monensin had more lethal effect against the parasite compared to its mild and reversible toxic effect on host cells at 0.1 µM concentration. Data from this study encourage further exploration of monovalent ionophores for repurposing as novel anti-toxoplasmosis leads. Using cell culture techniques, transwell system and two quorum sensing (QS) molecules produced by Pseudomonas aeruginosa (3-Oxo and PQS), a leading agent of nosocomial infection, the effect of exposure to these QS molecules on the ability of the parasite to cross the BBB endothelial cells was evaluated. The effects of 3-Oxo and PQS at a low and high concentration with and without T. gondii infection on hBMECs were also characterised. Both 3-Oxo and PQS increased hBMEC monolayer permeability and integrity through PRKCA gene up-regulation, slowly induced cell apoptosis and halted cell proliferation at the G0/G1 stage. Overall, these results did not support the hypothesis that QS molecules from P. aeruginosa facilitate T. gondii crossing of BBB into the brain. Taken together, this thesis has presented new findings on T. gondii interaction with a 2D BBB model represented by hBMEC culture in a Transwell system, identified new genes and miRNAs altered by infection, and showed the potential of monensin as treatment for T. gondii infection. These findings should facilitate further analysis of host-pathogen interactions in toxoplasmosis in preclinical animal models.